KONTRIBUSI GURU PAI DALAM MENUMBUHKAN KARAKTER KEPEMIMPINAN SISWA MELALUI KEGIATAN KEAGAMAAN DI SEKOLAH (Studi Kasus di SMP Al-Hikmah Balongrejo Badas Sumobito Jombang) - Dicca Shinta Noer Jannah; Iva Inayatul Ilahiyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Leadership character is an important aspect of student self-development that needs to be considered in the education system. One of the parties who has a crucial role in forming this character is the Islamic Religious Education (PAI) teacher. Through various religious activities at school, PAI teachers can instill strong leadership values in students. This research discusses the contribution of PAI teachers in developing student leadership character through religious activities at Al-Hikmah Balongrejo Badas Sumobito Middle School, Jombang. The focus of the research is: 1) What is the Leadership Character of students at Al-Hikmah Balongrejo Middle School?, 2) What are the Forms of Religious Activities at Al-Hikmah Balongrejo Middle School?, 3) What is the contribution of PAI Teachers in cultivating students' Leadership Character through religious activities at Al SMP -The lesson of Balongrejo?. This research uses a qualitative approach with a case study type of research. Data collection techniques were carried out using observation, interviews and documentation methods. The informants for this research consisted of the School Principal, PAI Teachers, and students. Data collected from observations and interviews were analyzed using data validity checking techniques through the source triangulation method. The research results show that: 1) Research shows that the leadership character of students at Al-Hikmah Balongrejo Middle School is good and will continue to be developed. 2) Forms of religious activities at Al-Hikmah Balongrejo Middle School such as congregational prayers, reading Yasin letters, istighosah. 3) The contribution of PAI teachers at Al-Hikmah Balongrejo Middle School in cultivating students' leadership character through religious activities and the application of Islamic values, so that students are ready to lead with noble morals.